Comparison of large and ultra-small delta c-14 measurements in core top benthic foraminifera from the Okhotsk Sea - Keigwin, L. D.; Gagnon, A. R. (Radiocarbon, 2015)
The radiocarbon activity of benthic foraminifera was investigated in surface sediments from a high deposition rate location at a depth of 1000 m in the Okhotsk Sea. Sediments were preserved and stained with Rose Bengal to identify foraminifera that contain cytoplasm. The benthic fauna at this site is dominated by large specimens of Uvigerina peregrina, and bulk samples (similar to 150 individuals) of stained and unstained specimens were dated. The stained sample was about 240 C-14 yr younger than the unstained, and the presence of bomb C-14 is inferred by comparison to water column data in the nearby open North Pacific. Using new methods, multiple measurements were also made on samples of three stained and unstained individuals (as small as 7 mu g C). Results are consistent with those from the bulk samples. This suggests that similar ultra-small measurements could be made at other locations to reveal the age distribution of individuals in a sediment sample in order to assess the extent of bioturbation and the presence of bomb C-14 contamination.
PT: J; TC: 1; UT: WOS:000351052600010